Description of Anemia Case on Referral Patients At Mother and Child Hospital Siti Hawa Padang in January – December 2018 - Herti Marni; Desmiwarti Desmiwarti (Universitas Andalas, 2020)
Anemia is the most common hematological disorder in pregnant women, primarily caused by iron deficiency. Many factors affect hemoglobin levels such as socioeconomic, educational level, age, parity, etc. Globally, there are 40.1% of women who experience anemia in pregnancy, with more than half due to iron deficiency.This study is a descriptive study using a cross sectional design with a population of anemic obstetric patients who were treated at Siti Hawa Hospital Padang from January 2018 to December 2018. All populations that met the inclusion criteria were taken as samples, so that 50 samples were obtained. Total population of hospitalized obstetric patient was 1994 patient.The results showed that the most obstetric patients with anemia found in 20-35 years old patients, in the second and third pregnancies. Most commonly found in non-bleeding patients with moderate degrees of anemia. The most patients came from Lubuk Begalung, Padang Timur, and Pauh. In addition, 3 patients were referred from outside the city of Padang, which are from the Mentawai Islands, Dharmasraya, and Pariaman.Keywords: anemia, age, parity, diagnosis, area